What is new in the psychology of chronic itch?. Issue 12 (13th August 2019) - Evers, Andrea W. M.; Peerdeman, Kaya J.; van Laarhoven, Antoinette I. M.
Abstract: Itch is often regarded as unpleasant or bothersome and is accompanied by symptoms of distress and impairments in daily life. The biopsychosocial model of chronic itch describes how psychological factors can contribute to the improvement or exacerbation of chronic itch and related scratching behaviour. Recent research underlines the important role of cognitive‐affective information processing, such as attention, affect and expectancies. This may not only play a role for acute itch states, but may particularly apply to the process of itch chronification, for example, due to the vicious cycle in which these factors shape the experience of itch. The present paper focuses on new insights into the relation between itch and the cognitive‐affective factors of attention, affect and expectancies. These factors are thought to play a possible aggravating role in itch in the long term and have received increasing attention in the recent empirical literature on maintaining and exacerbating factors for chronic physical symptoms. Possible psychophysiological and neurobiological pathways regarding these factors are discussed, as well as possible intervention methods.